Analysis of Body Work Posture in Midwives During Placental Retention - Ashari, Firdaus; Subodro, Rohmat (Sainteks, 2023)
The midwife's working posture when taking the placenta attached to the uterus of the laboring mother manually shows the body's posture which can cause musculoskeletal disorders. This research aims to know and study the assessment of the REBA method for midwife workers' posture in the prevention of musculoskeletal disorders. This research method is a type of observational analytic study that uses descriptive qualitative in total sampling among midwife workers. Data was collected using a REBA sheet. The results showed the results of the assessment using REBA with a final score of 13 has a level of risk "Very High" and requires immediate corrective action. This risk is caused by the back being bent and twisting laterally, the midwife's neck twisting laterally, the upper arm of the worker experiencing flexion, and the position of the arm is raised away from the body due to the position of the uterus being far and narrow. Suggestions given are efforts to control engineering, the provision of work procedures, and the procurement of healthy safety work.